Evaluation of Semen Quality of Free-Range Chickens After Addition of Putri Malu Leaf Herbal Extract (Mimosa pudica Linn) - Heru Suripta; Puji Astuti; Ina Nurtanti (Postgraduate, University of Mataram, 2023)
This research was conducted to determine the effect of female shy daughter (Mimosa pudica Linn) leaf extract supplementation on the semen quality of native chickens. In this study, 18 male native chickens aged approximately 1 year with an average weight of 2.0 kg were used, divided into 6 treatments, each with 3 replications, each consisting of 1 chicken. Basal feed in this study used BR-1 chicken feed produced by PT. Japfa Comfeed Indonesia Tbk. As an adjustment before treatment, the chickens were reared for 1 week with basic feed. As a control before being given treatment, sperm was taken from chickens and used as a control. Furthermore, the chickens began to be given treatment by giving shame daughter leaf extract supplementation. The study was conducted experimentally using a completely randomized design by allocating 18 free-range male chickens which were divided into 6 treatments, each treatment consisting of three replications, one chicken each. The conclusion of this study is that the supplementation of Putri Mal leaf extract as much as 0.50 cc to 2 cc per day per chicken can increase sperm count per ml of free-range chicken semen, viability, motility, thickness, and color density, while the volume and pH of semen do not experience change.